Implementasi Manajemen Teknologi Terhadap Penjualan Pulsa Pada Aplikasi Agen Pulsa Termurah: Studi Kasus Syaqila Cell - Siti Aisyah; Efni Yulia Santri Harahap; Nabila Ramadhani; Nurita Maha; Sella Fauziati Harlina; Siti Nur Khalizah Siregar (Literasi Nusantara Publisher, 2022)
The development of information technology, the current pulse filling transaction is not limited to using the SMS service, but can use an electric pulse filling application based on a credit agent application. Using this application is cheaper than topping up credit via SMS, besides that it can reduce errors in credit transactions. The method used in this community service activity is to teach about the application of the cheapest credit agent application which has various stages of activity arranged in a good schedule, namely: the preparation stage, the cheapest credit agent account creation stage, the training stage and the evaluation stage. After implementing and introducing the application to credit sellers, it was found that the Cheapest Credit Agent application had achieved the target of community service activities very well. This application will make it easier for counter owners to carry out credit sales transactions to their consumers. However, there are still obstacles experienced by selling credit in using this application, namely: 1) relatively small profits, 2) large enough capital, 3) many competitors or competitors, and 4) many customers who are in debt so that the profits should be increased to no visible results.